Pemanfaatan Garam Sebagai Bahan Stabilisasi Tanah Lempung di Kalimantan Tengah - Hendra Cahyadi; Nirwana Puspasari (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
Clay soils generally have low CBR and UCS values. Has poor characteristics. In Central Kalimantan the prices of CBR and UCS are low. The soil of clay by its predominance is fine grain easily by air. Some efforts to improve the soil are carried out by stabilizing the soil. One of the clay stabilizing ingredients that can be used is salt. The use of salt as a soil stabilizing agent can provide better benefits compared to other ingredients such as chemicals, sand and semen. The aim of the study was to determine the values of CBR and UCS Soil in Central Kalimantan before and after stabilization using salt. The study was conducted at the Land Mechanics Laboratory of the University of Muhammadiyah Palangkaraya. Samples of clay soil will be given in 6 (six) Regencies in Central Kalimantan Province. Tests carried out on clay are CBR tests and tests before and after stabilization with salt. The salt mixture released is 5, 10,15,20,25% and 30% of the dry weight of the clay. Based on the results of the study indicate that the original land CBR value between 3.90% to 4.75%, can be referred to as land that has a poor / low carrying capacity. Then after stabilizing 5% to 15%, the CBR value increased to reach 5% to 9%. However, after being mixed with salt as much as 20% to 30%, the soil CBR value is adjusted significantly. From this it can be explained that the CBR value reaches the maximum value with a salt rate of 10% to 15% of the weight of the soil.